4 PATIENT-TAILORED OUTPATIENT CHEMOTHERAPY REGIMENS FOR INOPERABLE ADVANCED METASTATIC PANCREAS CANCER. (1st January 2005) - Uckun, F. M.; Morar, S.; Olson, P.; Larson, J.; Eddy, L.; Qazi, S.
Abstract : Background: We treated 26 patients with advanced pancreas cancer, including 21 Stage IV patients, in an outpatient setting with multiple cycles of gemcitabine-based empirical chemotherapy regimens ("gemcitabine regimens"), such as gemcitabine monotherapy, gemcitabine + cisplatin, gemcitabine + 5-FU, and gemcitabine + Xeloda. Methods: Anatomic imaging or fusion technology with combined anatomic and functional imaging using CT/MRI scans fused with whole body PET scans was employed along with serial cancer marker level measurements to monitor response to therapy and tailor the treatments to each patient according to their treatment response. Patients who showed evidence of progression on a given gemcitabine regimen were switched to a different gemcitabine regimen. Results: Failure to respond to a particular gemcitabine regimen did not preclude objective responses to a different gemcitabine regimen. The average survival time was 14.3 months (n=26, 95% CI = 7.6-19.1, 18 died). The median survival time for Stage IV patients was 10.7 months (N=21; 95% CI = 6.9-19.1, 16 died). Notably, 47% of the patients survived more than one year following the diagnosis of distant metastases. Our results demonstrate that a significant portion of Stage IV pancreas cancer patients can live more than a year with an excellent quality of life on empirical gemcitabine-based outpatient treatments. By comparison, the overall average of the median survival times for more than 3, 000 advanced pancreas cancer patients treated on a clinical trial arm from 9 major published clinical studies was 8.4 months (weighted mean effect size = 0.73, Z test = 42.7, p < .0001). Conclusions: Fusion technology provides medical oncologists a powerful diagnostic tool for timely termination or modification of ineffective treatments. Patients with advanced pancreas cancer should be offered empirical patient-tailored chemotherapy as an alternative to the clinical trial and hospice options.